2020
DOI: 10.1038/s41598-020-59977-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative 3D imaging parameters improve prediction of hip osteoarthritis outcome

Abstract: Osteoarthritis is an increasingly important health problem for which the main treatment remains joint replacement. Therapy developments have been hampered by a lack of biomarkers that can reliably predict disease, while 2D radiographs interpreted by human observers are still the gold standard for clinical trial imaging assessment. We propose a 3D approach using computed tomography-a fast, readily available clinical technique-that can be applied in the assessment of osteoarthritis using a new quantitative 3D an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover, parameters describing subchondral trabecular bone structure in HOA (bone volume fraction, trabecular bone pattern factor, trabecular number, trabecular thickness, trabecular separation, and structure model index) that are often described by micro-CT are already adapted and evaluated in-vivo using multi-detector row CT 5052 . More recently it was elegantly demonstrated that use of clinical CT is a new and promising imaging tool in clinical assessment of both hip and knee OA 5355 . Thus, we believe that our method will further enrich current knowledge about subchondral bone involvement in pathogenesis of HOA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, parameters describing subchondral trabecular bone structure in HOA (bone volume fraction, trabecular bone pattern factor, trabecular number, trabecular thickness, trabecular separation, and structure model index) that are often described by micro-CT are already adapted and evaluated in-vivo using multi-detector row CT 5052 . More recently it was elegantly demonstrated that use of clinical CT is a new and promising imaging tool in clinical assessment of both hip and knee OA 5355 . Thus, we believe that our method will further enrich current knowledge about subchondral bone involvement in pathogenesis of HOA.…”
Section: Discussionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f 12 Changes in bone are part of the OA disease process. Recent studies have investigated the role of bone shape [19][20][21][22][23][24] , subchondral bone structure and texture [25][26][27][28] , and bone morphology in OA [29][30][31] as well as the interplay between subchondral bone changes and articular cartilage damage 32,33 .…”
Section: Imaging Of Bone Cartilage and Bone-cartilage Interactions In Oamentioning
confidence: 99%
“…From the AGES-Reykjavik cohort, further use of 3D shape modelling using CT has also enabled accurate 3D assessment of JSW distribution across the hip joint [20 ▪ ]. In a group of 80 cases and 187 controls, when combined with KL grade, these 3D metrics improved prediction of joint replacement by 18%, when compared with radiographic minimum JSW alone.…”
Section: Hip Imaging Studiesmentioning
confidence: 99%